2014
DOI: 10.17554/j.issn.2224-3992.2014.03.455
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Standard Anorectal Manometry and High Resolution Manometry Patterns in Dyssynergic Patients

Abstract: AIM:To compare dyssynergic sub type patterns between SARM and HRM. METHODS: Patients with dyssynergic defecation diagnosed by ARM that had maintained the same stool patterns and frequency were re-evaluated with HRM while on waiting list for biofeedback training. Anorectal resting and squeezing pressure on the bed and commode were analyzed and compared between the two modalities. Paired t-test was used to compare the pressures and sensations. RESULTS: 25 dyssynergic patients diagnosed with SARM (F=21, age 41±12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Our results indicate a good correlation in pressure metrics between the 2 techniques except for the length of sphincter and pressures during the bearing down on-commode. The agreement of DD types between the 2 techniques were poor, in keeping with a recently published data, 16 and this is probably because of better resolution of HRPT. Likewise, agreement between DD patterns described by Rao et al, 3 Rao and Singh, 4 and Ratuapli et al 5 (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our results indicate a good correlation in pressure metrics between the 2 techniques except for the length of sphincter and pressures during the bearing down on-commode. The agreement of DD types between the 2 techniques were poor, in keeping with a recently published data, 16 and this is probably because of better resolution of HRPT. Likewise, agreement between DD patterns described by Rao et al, 3 Rao and Singh, 4 and Ratuapli et al 5 (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Pressures derived from solid state and water-perfused anorectal manometry were shown in studies to correlate well, although these studies found higher anal sphincter pressures and a shorter sphincter with solid state HR manometry. [13][14][15][16] In these correlation studies, both techniques were performed on the same participants but on separate days, with intervals not clearly defined, and hence there is a potential for measurement bias due to changes in the anorectal physiology over time. Other factors to consider that might affect measurement include catheter design, number of sensors and diameter of the catheter, but these were eliminated with the current study design.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 27 principal studies published, 24 are in adults and 3 are in pediatric populations . Seventeen studies are in various patient groups (constipation: n = 8; constipation or fecal incontinence: n = 5; anal fissure, perineal descent, rectal cancer and Hirschsprung disease: all n = 1), of which only 4 are controlled the by inclusion of healthy volunteers .…”
Section: High‐resolution Anorectal Manometrymentioning
confidence: 99%
“…Three studies (all in patients) have compared parameters of anal sphincter function and anorectal coordination within individuals, measured using both contemporary HRAM/3‐D HDAM and also traditional water‐perfused manometry performed within the same study session . One study has compared ‘traditional’ solid‐state manometry with HRAM, and a further study subsampled HRAM data to derive traditional manometric recordings . All studies report good correlation of values between techniques (interclass correlation coefficients ranging from 0.42 to 0.9) .…”
Section: High‐resolution Anorectal Manometrymentioning
confidence: 99%
See 1 more Smart Citation